Las sociedades de gestión colectiva de Derecho de Autor en la era del streaming: retos y perspectivas - Cordova, Jorge (2025)
This article analyzes the role of the collective management organizations in the administration of copyright and related rights regarding the use of works, performances and phonograms, especially, on streaming platforms. Finally, analyzes the challenges that these entities have in the digital environment.